Identification of Ethylene Response Factors in Wheat Reveals That TaERF16-B Contributes to Salt Tolerance - Lei Zhang; Aili Wei; Jiating Chen; Lijuan Wu; Tian Li; Linyi Qiao (Plants)
Soil salinization is a major abiotic stressor that significantly reduces wheat yield. Identifying novel salt-tolerance genes and integrating them into wheat breeding programs can enhance wheat productivity in saline soils. Ethylene response factor (ERF) plays an important role in plant response to salt stress, and thus far, four wheat ERF genes have been identified to be involved in salt stress response. To systematically identify salt tolerance-related ERF genes in wheat, in this study, 213 ERF sequences were isolated from the whole genome of common wheat and classified into 54 members based on subgenome homology, named TaERF1 to TaERF54. Transcriptome sequencing results showed different expression patterns of TaERF members in leaves after 1, 6, 24, and 48 h of NaCl treatment. Based on association analysis, nine TaERF genes were correlated with the leaf salt injury index. Among them, five SNPs of TaERF16-B formed two haplotypes: Hap1 and Hap2. RT-qPCR results showed that the expression level of TaERF16-B was significantly higher in Hap2-typed germplasms than that in Hap1-typed germplasms after 1 and 6 h of NaCl treatment. A Kompetitive Allele-Specific PCR marker K52 was developed for genotyping TaERF16-B haplotypes, which further confirmed the significant correlation between TaERF16-B and salt tolerance-related phenotypes in mapping population and wheat germplasms. This study provides new genes and molecular markers for improving salt tolerance in wheat.